Production of renewable p-xylene from 2,5-dimethylfuran via Diels-Alder cycloaddition and dehydrative aromatization reactions over silica-alumina aerogel catalysts - Wijaya, Yanuar Philip; Suh, Dong Jin; Jae, Jungho (ELSEVIER SCIENCE BV, 2015)
We report the selective conversion of biomass-derived 2,5-dimethylfuran (DMF) to p-xylene (similar to 70% selectivity) through Diels-Alder cycloaddition and subsequent dehydration with silica-alumina aerogel (SAA) catalysts. The high activity of SAA can be attributed to its high surface area, large mesoporous volume, and high acid site concentrations. The conversion of DMF and the yield of p-xylene were strongly dependent on the silica alumina ratio of SAA. A higher aluminum content in SAA led to a progressive increase in the concentration of Bronsted acid sites and a corresponding increase in the p-xylene production rate. The effect of solvent on the production of p-xylene was examined, and it was found that the p-xylene production rate increases significantly in polar aprotic solvents (i.e. 1,4-dioxane). (C) 2015 Elsevier B.V. All rights reserved.
Keywords: TEREPHTHALIC ACID; BIOMASS; CONVERSION; ETHYLENE; AROMATICS; FUELS